2021
DOI: 10.3390/microorganisms9010171
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Marine Sponge-Associated Bacteria

Abstract: The misuse and overuse of antibiotics have led to the emergence of multidrug-resistant microorganisms, which decreases the chance of treating those infected with existing antibiotics. This resistance calls for the search of new antimicrobials from prolific producers of novel natural products including marine sponges. Many of the novel active compounds reported from sponges have originated from their microbial symbionts. Therefore, this study aims to screen for bioactive metabolites from bacteria isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…Our findings predict that marine sponges will continue to be a good source of novel antimicrobials (Anteneh et al 2021 ). This is especially the case when similarity analysis of these bacteria with type strains showed about 30% could potentially be new species, as has been found in other studies (Abdelmohsen et al 2010 ; Afonso de Menezes et al 2017 ; Ahn et al 2011 ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our findings predict that marine sponges will continue to be a good source of novel antimicrobials (Anteneh et al 2021 ). This is especially the case when similarity analysis of these bacteria with type strains showed about 30% could potentially be new species, as has been found in other studies (Abdelmohsen et al 2010 ; Afonso de Menezes et al 2017 ; Ahn et al 2011 ).…”
Section: Discussionmentioning
confidence: 66%
“…South Australian marine environments are a source of many sponge species with approximately 60% of them being endemic (Sorokin and Currie 2008 ). Variations in the chemical composition among sponges in South Australia have been reported (Sorokin et al 2007 ; Sorokin and Currie 2008 ), and it is expected that the associated bacteria could also be different either in terms of diversity or in the type of metabolites they produce (Anteneh et al 2021 ). Therefore, this study was designed to isolate bacteria from marine sponges, investigate factors affecting their relative diversity, and compare the diversity with a culture-independent approach.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of antimicrobial screening vary with respect to sample and methodology. Previous studies from sponges have reported hit rates of 8.4-41% without dereplication strategies [46][47][48]. Previous studies in soil and wastewater have reported hit rates of 1.3-42.4% [49,50].…”
Section: Antimicrobial Screeningmentioning
confidence: 99%
“…Microorganisms surviving in such antagonistic environments are likely to have unique metabolism and produce a variety of bioactive metabolites to suppress potential competitors. 4 Numerous studies have revealed that many antimicrobial compounds isolated from sponges are of spongeassociated microbial origin. 5 Thus, sponge-associated microorganisms, particularly bacteria and fungi, are regarded as a prospective source of novel antibiotics.…”
mentioning
confidence: 99%
“…5 Thus, sponge-associated microorganisms, particularly bacteria and fungi, are regarded as a prospective source of novel antibiotics. 4,5 It is well known that many biosynthetic gene clusters in microorganisms remain silent under standard laboratory conditions. 6 Co-culturing different microbes in a single environment is an effective approach to enhance the chemical diversity of metabolites.…”
mentioning
confidence: 99%